Review of In Situ Resource Utilization-Based Biocementation and Regolith Consolidation Techniques for Space Applications - Zhen Yan; Satoru Kawasaki (Buildings)
With the advancement of space exploration, the development of sustainable construction technologies has become essential for the establishment of enduring extraterrestrial habitats. In Situ Resource Utilization (ISRU) assumes a pivotal role by facilitating the use of indigenous materials on celestial bodies such as the Moon and Mars, thereby reducing reliance on terrestrial resources. This review provides a comprehensive analysis of the latest ISRU-based construction technologies, with particular emphasis on biocementation techniques. It further examines the challenges associated with the application of biocementation in extreme space environments and outlines prospective research directions. The continued advancement of ISRU technologies through interdisciplinary collaboration remains crucial for the realization of viable and cost-efficient extraterrestrial construction solutions.